Energy transfer and localization in optochemotronic emitter with electrodes modified using the Langmuir-Blodgett technique - Zholudov, Yu.T.; Rozhitskii, N.N. (Functional Materials, 2005)
Problems of the excitation energy transfer and localization under biradical recombination reaction have been considered for an optochemotronic emitter containing the working electrode with a layer of electrochemiluminophore molecules deposited thereon using the Langmuir-Blodgett technique. A couple of reagents including 9,10-diphenyl anthracene and p-terphenyl has been proposed for efficient transformation of electric energy into light at electrochemical reaction in the system mentioned. Рассмотрены вопросы локализации энергии возбуждения при бирадикальной рекомбинации в оптохемотронном излучателе с рабочим электродом, на поверхность которого методом Ленгмюра-Блоджетт нанесен слой молекул электрохемилюминофора. Предложена пара реагентов для эффективного преобразования электрической энергии в световую при электрохимической реакции в рассмотренной системе — 9,10-дифенилантрацен и n-терфенил. Розглянуто питання локалізації енергії збудження при бірадикальній рекомбінації в оптохемотронному випромінювачі з робочим електродом, на поверхню якого методом Ленгмюра-Блоджетт нанесений шар молекул електрохемілюмінофора. Запропоновано пару реагентів для ефективного перетворення електричної енергії у світлову при електрохімічній реакції у розглянутій системі — 9,10-дифенілантрацен та n-терфеніл.